Compilation Of Bio-Language Contextual Dictionary Media: Study Of The Meaning Of Arabic Lexicon In Rejang Language - Iswanto, Rahmat; Rini, Rini; Rinjiani, Vira (Ijaz Arabi Journal of Arabic Learning, 2025)
This article aims to design a bilingual dictionary, namely Arabic and Rejang, to preserve local culture and wisdom in Rejang Lebong Bengkulu Regency, Indonesia. This research is quantitative with a Research and Development (RD) approach. The RD approach used in this study follows the 4-D model developed by Thiagarajan, Semmel, and Semmel. The research results in this article show that the validation results of the bilingual dictionary, namely Arabic and Rejang, are categorized as very good from the validation value of the validators, namely, 4.6. In contrast, from the aspect of dictionary users with an average value of 4.2, it is categorized as good. The design of this bilingual dictionary is considered suitable for use by Arabic learners and the Rejang Lebong community, which is concerned with Arabic and Rejang.